Kerjasama Kelompok Tani Padi : Korelasi Faktor Internal dan Eksternal: Kerjasama Kelompok Tani Padi : Korelasi Faktor Internal dan Eksternal - Nastiti Winahyu; Erlin Widya Fatmawati; Khofifa Nur Atika; Retna Dewi Lestari; Ni Made Wirastika Sari (JURNAL ILMIAH AGRINECA, 2026)
This study aims to analyze the effectiveness of the role of rice farmer groups in Papar District, Kediri Regency by looking at the relationship between internal factors condition (cooperation between members) and external factors condition (cooperation with external parties and obtaining information) towards achieving group goals. The approach used was descriptive qualitative, with primary data collection (observations, interviews, questionnaires) and secondary data collection (literature, official reports). Data were analyzed using descriptive analysis and Spearman Rank correlation tests to measure the relationship between internal and external factors collaboration, group goals, and access to information. The research results showed that internal cooperation among members is significantly related to the achievement of group goals. Better cooperation increases the likelihood of group program success. External collaboration with agricultural extension workers, agricultural services, and business partners is associated with obtaining relevant information (assistance, extension, selling prices, production inputs). Overall, the role of rice farmer groups in the research locations was deemed effective in improving coordination, productivity, and support for their members. Practical value implications. The results of this research have practical value for Farmer groups, as a basis for strengthening internal cooperation and enhancing external collaboration. Government and agricultural extension workers, to formulate more targeted policies and extension programs. Agribusiness stakeholders, to expand partnerships that can facilitate market access, price information, and technology for farmers.